Spatiotemporally Controlling the Release of Biological Effectors Enhances Their Effects on Cell Migration and Neurite Outgrowth. Issue 9 (1st July 2020) - Xue, Jiajia; Wu, Tong; Qiu, Jichuan; Xia, Younan
Abstract: It is a major challenge to coordinate topographic cues from scaffolds with the on‐demand, sustained release of biological effectors to maximize their performance in tissue regeneration. Here, a system involving masked, photo‐triggered release of biological effectors from a temperature‐sensitive scaffold for augmented cell migration and neurite outgrowth is reported. The scaffold contains microparticles of a phase‐change material (PCM) sandwiched between two layers of electrospun fibers. The biological effectors are co‐loaded with a photothermal dye in the PCM microparticles. Under irradiation with a near‐infrared laser, the PCM will be melted to swiftly release the biological effectors. By imposing a photomask between the scaffold and the laser, only those microparticles in the irradiated region are melted, enabling a spatial control over the release. By adjusting the photomask, different regions of the scaffold can be sequentially irradiated at designated times, realizing on‐demand and sustained release of the biological effectors with spatiotemporal controls. In one demonstration, this method is used to accelerate the directional migration of NIH‐3T3 fibroblasts along the uniaxial or radial direction of fiber alignment by controlling the release of epidermal growth factor. In another demonstration, the release of nerve growth factor is managed to significantly promote neurite outgrowth from PC12 cells. Abstract : Scaffolds are fabricated by sandwiching microparticles consisting of a phase‐change material, a near‐infrared dye, and biological effectors between two layers of electrospun fibers. When sequentially exposing different regions of the scaffold to a near‐infrared laser through a tunable photomask, the biological effectors can be photothermally triggered for release with spatiotemporal controls to promote cell migration or neurite outgrowth.